Biochemical Composition and Seasonal Variations of the Madagascar Algae Eucheuma denticulatum (Solieriaceae, Rhodophyta) - Elando Fréda Zamanileha; Anne-Sophie Burlot; Thomas Latire; Christel Marty; Philippe Douzenel; Laurent Vandanjon; Nathalie Bourgougnon; Pierre Ravelonandro; Gilles Bedoux (Marine Drugs)
Although the density and diversity of seaweeds in Madagascar is particularly high, these resources are underexploited and they are not part of the local population’s eating habits. No study has been carried out on the nutritional properties and seasonal variation of Eucheuma species harvested in Madagascar. In this study, Eucheuma denticulatum was harvested monthly over two years (2021 and 2022) on the northeast coast of Madagascar (Sainte Marie Island). The compositional analysis revealed prominent sugars and minerals up to 41.0 and 39.5% dw, respectively. E. denticulatum showed slight variability over the seasons in the macroelements and oligoelements (Ca, K, Na, Mg, Fe, Mn) ranging from 22.8 ± 0.2 to 25.3 ± 0.1% dw in 2021 and 22.1 ± 0.3 to 26.5 ± 0.3% dw in 2022. Total amino acids varied from 2.3 ± 0.6 to 2.5 ± 0.6% dw during the two years. Seaweed extracts showed antioxidant activity by the in vitro method ranging from 2026 ± 2 to 2998 ± 4 μg.mL−1 in 2021, and from 1904 ± 2 to 2876 ± 4 μg.mL−1 in 2022. Finally, the principal component analysis (PCA) showed a correlation between protein content and environmental parameters. The nutritional characteristics therefore confirmed that E. denticulatum could potentially be used as a nutritious and functional food and could be incorporated in the diet of local populations.